Pemanfaatan Aplikasi Quizizz sebagai Media Digital untuk Meningkatkan Minat Belajar Sekolah Menengah Atas (SMA) - Ayu Nita Singgi; Resilvia Mangadi; Naomi, Naomi; Mandacan, Meriyana; Ronaldo Stefanus (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines how the use of Quizizz as a digital learning media has great potential to enhance the learning interest of senior high school students. Quizizz provides an interactive learning experience through game-based quizzes that are engaging, easy to use, and accessible online. Features such as appealing visual design, point systems, gamification elements, and instant feedback help students become more active and motivated during the learning process. The purpose of this study is to analyze the effectiveness of using Quizizz in increasing students’ learning interest across various subjects at the senior high school level. The research methods include observation, the implementation of interactive quizzes, and the distribution of learning-interest questionnaires administered before and after using the media. The results indicate that Quizizz creates a more enjoyable, competitive, and participatory learning atmosphere, contributing significantly to the improvement of students’ learning interest. Therefore, Quizizz can be considered an effective digital learning alternative to support the teaching and learning process in senior high schools.